Three‐Component Acylation/Peroxidation of Alkenes through Visible‐Light Photocatalysis. Issue 40 (22nd October 2021) - Zhao, Dengyang; Pan, Yingjie; Chen, Xiaoyun; Han, Ying; Yan, Chaoguo; Shi, Yaocheng; Hou, Hong; Zhu, Shaoqun
Abstract: A three‐component acylation/peroxidation of alkenes through visible‐light photocatalysis was described. The acyl radical was generated by a hydrogen atom transfer process and enabled the radical addition and peroxidation. Various indole‐3‐carbaldehyde and styrene derivatives were subjected to the current visible light photochemical conditions, delivering β‐peroxy‐ketones in moderate to good isolated yields. Abstract : Visible‐light photocatalyzed three‐component acylation/peroxidation of alkenes was described, for the construction of β‐peroxy‐ketones in moderate to good isolated yields.